Hubungan Antara Pengetahuan Tentang Perubahan Fisik pada Masa Pubertas dengan Tingkat Stres Remaja Putri di SMP Negeri 10 Kupang - Toumeluk, Ega Monica; Soegianto, Sugi Deny P.; Woda, Rahel Rara; Legoh, Dickson (Cendana Medical Journal, 2023)
Background : Physical changes are certain things that will be faced when individuals reach adolescence. This phase causes feelings from fear, shame, anxiety, to psychological stress, especially in adolescent girls when they first face menstruation. Adolescent knowledge related to these physical changes is thought to affect the stress level of adolescents. Objective : To determine the relationship between knowledge about physical changes during puberty and the stress level of adolescent girls at SMP Negeri 10 Kupang. Methods : An observational analytic study with a cross sectional design involving 108 respondents which was carried out at SMP Negeri 10 Kupang, East Nusa Tenggara in August 2022. The research data was obtained through a Questionnaire Level of Knowledge of Physical Changes and DASS 42. Results : From 108 respondents, it was found that 50% of respondents had suffiicient knowledge about physical changes during puberty and 50,9% of respondents did not experience stress. The results of the analysis showed that there was a relationship between the level of knowledge about physical changes during puberty and stress levels (p < 0,02). Conclusion : There is a relationship between the level of knowledge about physical changes during puberty with stress levels.